2020
DOI: 10.4314/tjpr.v19i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, colony formation and anti-migratory effects of <I>Spilanthes acmella</I> (Asteraceae) aerial extract on MCF-7 cells and its cream formulation

Abstract: Purpose: To determine anti-breast cancer activities of Spilanthes acmella (S. acmella) extract.Methods: S. acmella was macerated with 95% ethanol. Phenolic, flavonoid content and antioxidant activity of the extract were assessed using Folin  Ciocalteu method, aluminum chloride (AlCl3) colorimetric method and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, respectively. Cytotoxicity, colony formation and cell migration suppression on MCF-7 cells, representing anti-breast cancer effects, were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…Boontha et al [ 81 ] reported the anticancer effect of S. acmella extract on MCF- 7 cells. S. acmella extracts contained TPC (62.8 ± 5.2 mg GAE/g), TFC (375.6 ± 20.1 mg rutin equivalent/g) and DPPH with IC 50 (1.2 ± 0.1 mg/mL).…”
Section: Antioxidant Properties Of S Acmellamentioning
confidence: 99%
“…Boontha et al [ 81 ] reported the anticancer effect of S. acmella extract on MCF- 7 cells. S. acmella extracts contained TPC (62.8 ± 5.2 mg GAE/g), TFC (375.6 ± 20.1 mg rutin equivalent/g) and DPPH with IC 50 (1.2 ± 0.1 mg/mL).…”
Section: Antioxidant Properties Of S Acmellamentioning
confidence: 99%
“…The presence of growth factors at the scratch border triggers cells to close the scratch. [27][28][29] Plate 1: Morphological changes of the MCF-7 HER2 cells after treatment with 10 and 100 μg/mlethyl acetate fraction for 24 h…”
Section: Scratch Wound Healing Assay Of Fractionsmentioning
confidence: 99%
“…Spilanthes acmella extract possesses anti-breast cancer activities that inhibit colony formation and metastasis in human t MCF-7 breast cancer cells [134]. Researchers have studied the anti-cancer effects of S. acmella extract on two types of cancer cell lines: colon (HT-29) and liver (HEP-2).…”
Section: Eudesmanolide (Spilanthes Acmella and Taraxacum Officinale)mentioning
confidence: 99%